Zanobatus maculatus, a new species of panray from the Gulf of Guinea, eastern central Atlantic (Elasmobranchii: Batoidea: Zanobatidae) - Séret, Bernard (Zootaxa, 2016)
A new species of panray, Zanabatus maculatus sp. nov., is described from 12 type specimens collected in the Gulf of Guinea (Eastern Central Atlantic). The new species is distinguished from its sympatric congener, the striped panray Zanobatus schoenleinii, by its smaller size, heavier thorn pattern, spearhead-shaped dermal denticles and maculate colour pattern.